AGILE METHODS: BETWEEN CATEGORICAL IMPERATIVES AND LEAN PRODUCTION. - SUCCI, GIANCARLO (Communications of the ACM, 2006)
The article discusses what the author describes as the "lean revolution" in management, which was created to change manufacturing in the 1950s. This management style attempts to eliminate any non-essential tasks from the manufacturing process. The author discusses the relationship between the "lean revolution" and "agile" management. The article argues that documentation of the computer software development process is essential as software programs can last for twenty years or more and it is necessary to have complete documentation.